2020
DOI: 10.1111/bcp.14500
|View full text |Cite
|
Sign up to set email alerts
|

Impairment of endoxifen formation in tamoxifen‐treated premenopausal breast cancer patients carrying reduced‐function CYP2D6 alleles

Abstract: Aims: Tamoxifen is bioactivated to endoxifen by polymorphic CYP2D6-dependent metabolism. Here, endoxifen levels were compared to CYP2D6 diplotypes, tentative target concentrations and side effects. Methods: In total, 118 Swedish premenopausal breast cancer patients diagnosed 2006-2014, with ongoing postoperative tamoxifen treatment January 2017, were included. Biobanked DNA from peripheral blood was used for CYP2D6 genotyping by TaqMan real-time polymerase chain reaction (CYP2D6*1, *3, *4, *5, *6, *9, *10, *41… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
27
1

Year Published

2020
2020
2023
2023

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 23 publications
(31 citation statements)
references
References 41 publications
3
27
1
Order By: Relevance
“…Data from several in vitro and in vivo reports argue that the extent of metabolic activity decrease caused by the CYP2D6*10 9,10 and CYP2D6*41 7,11–13 alleles is > 50% and in compliance, the recent consensus guidelines decreased the metabolic activity score approximation for CYP2D6*10 from 50% to 25% 5 . The results here obtained, which are based on a very large number of patients, support these data and argue that the decrease in metabolic activity encoded by the CYP2D6Decr alleles is indeed lower than 50% compared with the one of CYP2D6Norm .…”
Section: Discussionsupporting
confidence: 84%
“…Data from several in vitro and in vivo reports argue that the extent of metabolic activity decrease caused by the CYP2D6*10 9,10 and CYP2D6*41 7,11–13 alleles is > 50% and in compliance, the recent consensus guidelines decreased the metabolic activity score approximation for CYP2D6*10 from 50% to 25% 5 . The results here obtained, which are based on a very large number of patients, support these data and argue that the decrease in metabolic activity encoded by the CYP2D6Decr alleles is indeed lower than 50% compared with the one of CYP2D6Norm .…”
Section: Discussionsupporting
confidence: 84%
“…Taken together, these studies [70,71] confirmed that CYP2D6 metabolizer status is a strong determinant of endoxifen plasma concentration and that increasing CYP2D6 allele activity correlates with increasing plasma levels.…”
Section: Factors Affecting Endoxifen Levelsmentioning
confidence: 58%
“…However, this threshold was questioned, because the study was not designed to determine this endoxifen threshold [68,69]. In 2020, in all homozygous carriers of CYP2D6 non-functional alleles, but also in carriers of two reduced function alleles, significantly reduced endoxifen levels were observed [70]. A total of 118 Swedish premenopausal breast cancer patients genotyped for nine different allelic variants using blood as a source of genomic DNA showed that the endoxifen concentration in 32% of patients did not reach this putative threshold.…”
Section: Factors Affecting Endoxifen Levelsmentioning
confidence: 99%
See 1 more Smart Citation
“…These inconsistencies may have important clinical implications for genotype-based dose recommendations of many psychiatric drugs, as CYP2D6 generally plays a key role in the metabolism of such agents. However, the same concerns CYP2D6 drug substrates from other therapeutic classes, e.g., tamoxifen, where Thorén et al (2020) reported a significantly stronger impact of CYP2D6*41 than CYP2D6*10 on the CYP2D6-mediated bioactivation to endoxifen (Thorén et al, 2020), which mainly mediates the preventive effect on breast cancer recurrence.…”
Section: Discussionmentioning
confidence: 99%